Mobile phones in the spread of unreliable information on Twitter: evidence from the 2017 French presidential campaign. (September 2021) - Figeac, Julien; Ratinaud, Pierre; Smyrnaios, Nikos; Cabanac, Guillaume; Fraisier-Vannier, Ophélie; Salord, Tristan; Seffusatti, Fanny
This article analyzes the spread of unreliable information on Twitter during the 2017 French presidential campaign, focusing on the use of mobile phones with regard to information-sharing behavior. The corpus is composed of 38, 346, 765 tweets, posted by 2, 163, 812 supporters of the five main French political parties, from November 25, 2016 to May 12, 2017. We examine more precisely a sub-corpus of tweets (13, 044, 619) containing links to external information sources, in order to evaluate the different types of information sources and their reliability. Our research shows that information-sharing behavior within Twitter in France is generally based on reliable information sources, produced by journalists and professional media. However, we highlight that smartphone users tended to share a greater amount of user-generated content, as well as articles from a wider range of alternative political information sources (blogs, activists' websites); such sources were most likely to publish unreliable information. Thus it appears that users of mobile phones tend to share more unreliable news than those who use Twitter from a computer web browser. Further, we show that this "device effect" on the spread of unreliable information is primarily amplified among the practices of one political community—namely, the far-right party and its network of supporters—which is more likely to organize debate around a larger number of unreliable references. We are claiming here that the design-based interoperability of these unreliable political news and social media applications helps to understand why the French far-right community shared more unreliable information from the Twitter application.